Job Mobility, Tenure, and Promotions in Political Science PhD-Granting Departments, 2002–2017: Cohort, Gender, and Citation-Count Effects. Issue 4 (October 2019) - Kim, Hannah June; Grofman, Bernard
ABSTRACT: Using updated data from 2002 and 2017 on the political science discipline, we show how the cohort and gender composition of US PhD-granting departments has changed dramatically over time. Integrating 2002 and 2017 data, we examine overall patterns and gender differences in job mobility, tenure and promotion, and university prestige level among non-emeritus 2002 faculty, controlling for cohort effects. Even with this control, we find strong gender effects in some of these success dimensions. We then introduce another variable, citation counts, and find that women are consistently less cited than men, with important variations in the pattern across different cohorts. A control for citation counts show that some of these gender differences tend to disappear and we consider possible explanations for these findings.